Development of English Vocabulary Webpage for EFL Students: Pengembangan Laman Kosakata Bahasa Inggris untuk Siswa EFL - Agnetia Evelina; Abdul Syahid; Hesty Widiastuty (English Language Education Department, Universitas Majalengka, 2024)
This research aims to develop a digital tool to enhance the vocabulary learning experience for EFL students. The method used was Research & Development with the ADDIE model, and the subjects were grade 7 students. Data collection using questionnaires and validation tests. Using User Experience Questionnaire to analyse the level of user satisfaction in using learning media. Validation was carried out by two experts, namely media experts with 96% results and material experts with 93% results. Trial results showed that the small group had an average 'excellent' score of 2.36 and the lowest 'novelty' score of 1.55, while the large group obtained an average 'excellent' score of 1.77 and the lowest 'novelty' score of 0.70. The application of the ADDIE model is proven to have a positive impact on digital media in vocabulary learning. Practically, the increased student engagement and support for self-directed learning that teachers and students can gain from this webpage and this webpage can be used as an additional tool that suits the needs of modern education.